Hazardous chemicals in the polymer industry - Cheremisinoff, Nicholas P. (Marcel Dekker, 1995)
How to use the Handbook -- Monomers of synthetic rubbers -- Vulcanizing agents -- Accelerators and activators -- Mineral fillers, activators and dusting agents -- Antioxidants, stabilizers and fire retardants -- Retarders -- Blowing agents --Oils, plasticizers, lubricants, solvents and mold release agents